From Wicksell to Le Bourva to Modern Monetary Theory: A Wicksell connection - Dirk Ehnts; Nicolas Barbaroux (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2017)
In the aftermath of the Great Financial Crisis (GFC), and within the context of significant macroeconomic imbalances in the world economy, economists have shown renewed interest in the way central banks and financial systems work. The rise of Modern Monetary Theory (MMT) has relied on the examination of balance sheets, which has led to advancements in the understanding of the nuts and bolts of the financial system and the fundamental role of taxes, reserves, and deposits. While the school is associated with Post-Keynesian economics, we make the case that it could just as well be called Post-Wicksellian. The aim is not to argue for or against some label, but to make explicit the Wicksellian connection. In doing this, we bring forward old discussions and insights, which can be integrated into recent debates. MMT authors emphasize the importance of endogenous money and the examination of assets and liabilities in balance sheets. In our inquiry, we demonstrate that a horizontalist approach - adopted by MMT scholars - was already present in Wicksell (1898) and in the writings of French economist Jacques Le Bourva (1959, 1962). We examine the essential publications of the two authors and compare their views with the insights of MMT. By doing this, we hope to show continuity in monetary thought. MMT should not be seen as an intruder from the outside of monetary theory, but rather as a continuation and expansion of certain ideas that have long been part of the discipline. Identifying areas of disagreement between the three views should help bring clarity to the issues that are still disputed.
Keywords: E4; E51; E58; 330; central banking; monetary policy; discretionary practices; Wicksell; Modern Monetary Theory; MMT